RESULTS OF RESEARCH INTO CO LOA CITADEL (2007 - 2014): MATERIALS AND DISCUSSION - Trịnh Hoàng Hiệp (Tạp chí Khoa học Đại học Đà Lạt)
The results from the excavation at Co Loa citadel (Donganh district, Hanoi) in 2007 - 2014 provide many new data on the dates of its building stages, construction techniques, and other architectural features. Co Loa citadel, built by King An Duong, inherited a previous one - the citadel/ramparts of a defensive village from a chiefdom of the late Dong Son period. The citadel built by King An Dương was many times larger than the previous one. Therefore, the workload must have been of a level indicative of a social system with a centralized politic entity functioning as a primitive state. The research into the building techniques, scale, and architecture of the citadel demonstrates the Vietnamese style, which was very different from the Han style. After the period of King An Duong, the middle and outer ramparts of Co Loa citadel were renovated several times, including once under the Le period. This article describes research materials obtained at Co Loa citadel from 2007 to 2014. A discussion about techniques and stages of building the ramparts, the characteristics and chronology of the citadel, and, especially, the relationship between the history of the citadel and the process of state formation in the King An Duong era will be presented.